Single-molecule imaging reveals replication fork coupled formation of G-quadruplex structures hinders local replication stress signaling - Lee, Wei Ting C.; Yin, Yandong; Morten, Michael J.; Tonzi, Peter; Gwo, Pam Pam; Odermatt, Diana C.; Modesti, Mauro; Cantor, Sharon B.; Gari, Kerstin; Huang, Tony T.; Rothenberg, Eli (Nature communications, 2021)
Guanine-rich DNA sequences occur throughout the human genome and can transiently form G-quadruplex (G4) structures that may obstruct DNA replication, leading to genomic instability. Here, we apply multi-color single-molecule localization microscopy (SMLM) coupled with robust data-mining algorithms to quantitatively visualize replication fork (RF)-coupled formation and spatial-association of endogenous G4s. Using this data, we investigate the effects of G4s on replisome dynamics and organization. We show that a small fraction of active replication forks spontaneously form G4s at newly unwound DNA immediately behind the MCM helicase and before nascent DNA synthesis. These G4s locally perturb replisome dynamics and organization by reducing DNA synthesis and limiting the binding of the single-strand DNA-binding protein RPA. We find that the resolution of RF-coupled G4s is mediated by an interplay between RPA and the FANCJ helicase. FANCJ deficiency leads to G4 accumulation, DNA damage at G4-associated replication forks, and silencing of the RPA-mediated replication stress response. Our study provides first-hand evidence of the intrinsic, RF-coupled formation of G4 structures, offering unique mechanistic insights into the interference and regulation of stable G4s at replication forks and their effect on RPA-associated fork signaling and genomic instability. In the genome, repetitive guanine-rich sequences have the potential to spontaneously fold into non-canonical DNA secondary structures known as G-quadruplex (G4). Using novel single-molecule imaging approaches, the authors reveal that G4 formation within active replication forks locally perturb replisome dynamics and damage response signaling, which require RPA and FANCJ for regulation.